Vibrational signals are species‐specific and sex‐specific for sexual communication in the tea leafhopper, Empoasca onukii. Issue 4 (26th January 2023) - Zhang, Huining; Bian, Lei; Cai, Xiaoming; Yao, Qi; Fu, Nanxia; Shan, Yao; Chen, Zongmao
Abstract: Empoasca onukii Matsuda (Hemiptera: Cicadellidae) is the primary pest of tea gardens, but the species' sexual communication and mating behavior is currently unclear. A similar species, Empoasca vitis Göthe, had been reported to use vibrational signals for mating communication, so we studied these two aspects from the perspective of biotremology. First, laser vibrometry detected both males and females could emit vibrational signals that are sex specific. Females emitted one signal type (the female signal), and males emitted two signal types: the male calling signal and the male courtship signal. Compared with the male signals, the female signal has a simpler structure, lower dominant frequency, and shorter length. Second, the vibrational signals of E. onukii play a decisive role in sexual communication. The male emits calling signals and then recognizes the female based on her reply signal; after establishing a duet with the female, the male emits a series of courtship signals, and then continually locates and approaches the female according to her reply signals, and finally attempts to copulate. Third, vibrational signals of E. onukii are species‐specific. Comparing E. onukii and E. vitis, there are differences in three aspects: the emitting behavior of female signals, the types of male signals, and the structure of male and female signals. We conclude that E. onukii uses sex‐ and species‐specific vibrational signals for sexual communication. Abstract : We analyzed the sexual communication of Empoasca onukii (Hemiptera: Cicadellidae) from the perspective of biotremology. We established that E. onukii emits sex‐ and species‐specific vibrational signals. Females emitted one signal type, whereas males emitted a calling and a courtship signal. Empoasca onukii and E. vitis differed in emission of female signals, male signal types, and male and female signal structure. The vibrational signals of E. onukii play a major role in the identification and localization stage during pair formation.